Linking global youth tobacco survey (GYTDS) data to tobacco control policy in Turkey – 2003 and 2009 - Erguder, Toker; Polat, Halil; Arpad, Ceylan; Khoury, Rula Nabil; Warren, Charles W; Lee, Juliette; Lea, Veronica (Central European Journal of Public Health, 2012)
Objective: The purpose of this paper is to use data from the Global Youth Tobacco Survey (GYTS) conducted in Turkey in 2003 and 2009 to examine changes in tobacco use and important tobacco control measures. Methods: The GYTS were conducted in grades 7–9 in 2003 and 7–10 in 2009 in Turkey. Data in this paper are limited to 13 to 15 year old students. A total of 15,957 students from 202 schools participated in 2003 and 5,054 students from 69 schools participated in 2009. The overall response rate was 92.1% in 2003 and 87.5% in 2009. Results: Between 2003 and 2009 current cigarette smoking did not change significantly for either boys (9.4% to 10.2%) or girls (3.5% to 5.3%). Current cigarette smoking was higher among boys than girls in 2003 and in 2009. In 2009, half of students reported they had been exposed to second hand smoking (SHS) at home and 80% reported they had been exposed to SHS in public places. Three in ten students reported they had been exposed to pro-tobacco advertising in newspapers or magazines; one in ten had an object with a cigarette brand logo on it; and 7% had been offered free cigarettes by a cigarette company representative. Two-thirds of current cigarette smokers reported that they wanted to stop smoking; and almost two-thirds had been taught in school in the past year about the dangers of smoking. Conclusion: Passing and implementing the Law No. 4207 on Prevention of Hazards of Tobacco Products, ratifying the World Health Organization Framework Convention on Tobacco Control (WHO FCTC), raising tax on tobacco, and requiring pictorial warning labels were important steps forward for tobacco control in Turkey. However, as to the tobacco control much work yet to be accomplished including developing an effective enforcement plan for all tobacco control efforts.
Keywords: Tobacco Smoke Pollution; inzerce jako téma; znečištění tabákovým kouřem; Smoking; zdravotní politika; Female; Prevalence; ženské pohlaví; Adolescent Behavior; Adolescent; kouření; Nicotiana; lidé; Smoking Prevention; odvykání kouření; Turkey; Advertising; Sex Factors; Health Policy; prevalence; Turecko; prevence kouření; Male; sexuální faktory; mladiství; Health Knowledge, Attitudes, Practice; Mass Media; mužské pohlaví; tabák; hromadné sdělovací prostředky; chování mladistvých; Smoking Cessation; Humans